2016
DOI: 10.1016/j.healun.2016.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Lung transplantation following coronary artery bypass surgery—improved outcomes following single-lung transplant

Abstract: Although LTx after CABG is uncommon, it is increasingly performed in the current era. Single right LTx is the most common procedure performed in patients with prior CABG. CABG before LTx is an independent predictor of mortality at all time points and is driven by increased mortality in patients receiving bilateral LTx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 8 publications
1
23
0
Order By: Relevance
“…This is consistent with previous studies where the risk of early complications was higher among patients with a history of prior thoracic surgery . Although the long‐term survival did not seem to be impacted in some of the studies, more recent studies on larger cohorts found that history of coronary artery bypass grafting (CABG) was strongly associated with significantly increased mortality especially after bilateral LT . Interestingly, the increased risk of mortality was not seen after a single right or single left LT in this study.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous studies where the risk of early complications was higher among patients with a history of prior thoracic surgery . Although the long‐term survival did not seem to be impacted in some of the studies, more recent studies on larger cohorts found that history of coronary artery bypass grafting (CABG) was strongly associated with significantly increased mortality especially after bilateral LT . Interestingly, the increased risk of mortality was not seen after a single right or single left LT in this study.…”
Section: Discussionsupporting
confidence: 92%
“…The presence or absence of CAD could be included as a variable on the UNOS data sheet and therefore be examined with nationally powered statistics. A good example of a nationally powered study is the analysis by McKellar et al, which showed that patients who previously underwent CABG followed by an LT had worse survival at 5 years (HR, 2.54; P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Several single‐center studies have shown that the presence of CAD in LT recipients does not increase the rate of perioperative cardiac events or significantly alter survival . Only a few studies have shown an increase in perioperative cardiovascular events or a change in survival . The United Network for Organ Sharing (UNOS) gathers data about previous cardiac surgical procedures such as coronary artery bypass grafting (CABG) but does not record the presence or absence of CAD or the presence of prior stenting.…”
Section: Introductionmentioning
confidence: 99%
“…While I agree that prior PCI or CABG alone should not preclude transplant candidacy, we should take these prior interventions into account when discussing multiple comorbidities in the elderly patients with lung transplantation. One recent largest retrospective study using the United Network for Organ Sharing Standard Transplant Analysis and Research database suggests that perhaps patients with prior CABG should be candidates only for single lung transplant , which is basically in line with our current strategy where the option for single lung transplant is also prioritized for those elderly patients who need concurrent CABG because of their severe CAD that precludes a PCI option with dual antiplatelet therapy because of their closing window for transplantation.…”
Section: Review Of the Literaturementioning
confidence: 72%